The value of tibial mounted inertial measurement units to quantify running kinetics in elite football (soccer) players. A reliability and agreement study using a research orientated and a clinically orientated system - Hughes, T.; Jones, R. K.; Starbuck, C.; Sergeant, J. C.; Callaghan, M. J. (Journal of Electromyography and Kinesiology, 2019)
In elite football, measurement of running kinetics with inertial measurement units (IMUs) may be useful as a component of periodic health examination (PHE). This study determined the reliability of, and agreement between a research orientated IMU and clinically orientated IMU system for initial peak acceleration (IPA) and IPA symmetry index (SI) measurement during running in elite footballers. On consecutive days, 16 participants performed treadmill running at 14kmph and 18kmph. Both IMUs measured IPA and IPA SI concurrently. All measurements had good or excellent within-session reliability (intraclass correlation coefficient (ICC2,1) range = 0.79-0.96, IPA standard error of measurement (SEM) range = 0.19-0.62 g, IPA SI SEM range = 2.50-8.05%). Only the research orientated IMU demonstrated acceptable minimal detectable changes (MDCs) for IPA at 14kmph (range = 7.46-9.80%) and IPA SI at both speeds (range = 6.92-9.21%). Considering both systems, between-session IPA reliability ranged from fair to good (ICC2,1 range = 0.63-0.87, SEM range = 0.51-1.10 g) and poor to fair for IPA SI (ICC2,1 range = 0.32-0.65, SEM range = 8.07-11.18%). All MDCs were >10%. For IPA and SI, the 95% levels of agreement indicated poor between system agreement. Therefore, the use of IMUs to evaluate treadmill running kinetics cannot be recommended in this population as a PHE test to identify prognostic factors for injuries or for rehabilitation purposes.